The elite's collective subjectivities of the history of ethnic politics in Malaysia - Xia, Nan; Lee, Yok Fee; Ab Halim, Adlina (Routledge, 2019)
Malaysia is one of the multi-ethnic, multi-cultural and multi-religious countries in Southeast Asia. Due to the pluralistic nature of Malaysia, it has a political structure based on ethnic politics. The ethnic preferential policies affected most domains of this country. The objective of this article is to examine the origin and background of ethnic politics in Malaysia. Findings of this study indicate that, ethnic politics originated during the British colonial period, it became a tool used by the Barisan Nasional for the legitimacy of regime. Moreover, ethnic politics in Malaysia today is intertwined with religion. Besides, there is the dilemma of the choice between the interest of certain ethnic group and national interests. However, with the opposition coalition Pakatan Harapan won the election in 9th May, UMNO-led BN lost power and interrupted its 61 years control, which leaves us an interesting topic to think about the future of Malaysian ethnic politics.